Direct Sulfenylation of Imidazoheterocycles with Disulfides in an Iodine–Hydrogen Peroxide System - Ji, Xiao-Ming; Zhou, Shu-Juan; Chen, Fan; Zhang, Xing-Guo; Tang, Ri-Yuan (Synthesis, 2015)
Imidazoheterocycles undergo efficient and regioselective sulfenylation with disulfides using the iodine/hydrogen peroxide system in ethanol at 25 °C. This green strategy tolerates a wide range of functional groups to afford diverse sulfenylated imidazoheterocycles in high yields. Moreover, the fipronil (a pesticide) skeleton can be readily attached to imidazoheterocycles using this strategy, which is significant in drug development.
Keywords: iodine; sulfenylation; disulfide; imidazothiazole; imidazopyridine